STUDIES ON EFFECT OF CEFOTAXIME AND TERMINALIA CHEBULA ON ESCHERICHIA COLI - ALPA RABADIA; S.D. KAMAT; D.V. KAMAT (International Journal of Pharma and Bio Sciences, 2013)
Infections caused by drug resistant Gram-negative bacteria are increasing day-by-day. An alternative mode of treatment needs to be considered to overcome the problem. With this aim in mind, the effect of Cefotaxime and aqueous extract of Terminalia chebula was studied on Escherichia coli by using Disc Diffusion Method and β-galactosidase assay. Disc Diffusion Method showed synergistic interaction between Cefotaxime and the aqueous extract of Terminalia chebula against Escherichia coli. The mode of action of the combination on Escherichia coli was evaluated using β-galactosidase assay. An increase in the level of β-galactosidase enzyme was observed in the cell suspension treated with the combination as compared to the controls. These results suggest that the active components present in the aqueous extract of Terminalia chebula should be an area of further in-vivo research so as to find leads of compounds which can act in combination with antibiotics.